Social Economy, Economic Crisis and Welfare State Restructuration: Spanish case - Inglada Galiana, Elena; Pérez Chinarro, Emilio; Manuel Sastre, Jose (Cooperativismo & Desarrollo, 2020)
Objective: This article aims to establish a historical and current link between the evolution of the welfare state, the social economy and economic crises. From this general objective, another more concrete objective can be deduced: to draw the links between the economic recession in 2008 and the consequences on the welfare state in Spain. Methodology: this research is carried out with secondary sources, through the literature review of theoretical aspects of the welfare state and the social economy. The consequences of the recession have been analyzed, examining different areas of action corresponding to the main areas that make up social policy, mainly housing, including various indicators —foreclosures, evictions or the GDP of the Autonomous Communities—.